Sclerosurgical treatment of the ruptured abdominal aortic aneurisms - B. S. Sukovatykh; L. N. Belikov; M. B. Sukovatykh; A. I. Itinson (Вестник хирургии имени И.И. Грекова)
The objective of the study is to assess the efficacy of the invented in the clinic technique of sclerosurgical treatment of the ruptured abdominal aortic aneurisms.Material and methods. The analysis of the treatment of 40 patients with ruptured abdominal aortic aneurism was done. All patients were divided into two groups consisted of 20 patients. The first group of patients were treated using conventional technique. Patients from the second group were treated using sclerosurgical treatment. The aneurysm was neither opened nor resected. The aneurism was punctured and injected 4 ml of 70 % ethanol under ultrasound guidance.Results. The second group of patients had decreased both the postoperative complications and mortality rate by 10 % and 30 % respectively.Conclusion. The original technique of sclerosurgical treatment of the ruptured abdominal aortic aneurisms is effective and pathogenically supported.